LEARNING TO WRITE EXPLANATORY TEXT USING THE PICTURE-TO-PICTURE METHOD FOR STUDENTS OF MTs NURUL HIKMAH BEKASI - Sigit Widiyarto (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
Learning to write for some students is still difficult. Writing requires practice and skill acquisition like vocabulary. Appropriate and effective methods also determine the success of learning to write. One method that emphasizes collaborative learning is the picture-to-picture cooperative method. The research in this paper used the Kemmis and McTaggart classroom action methods through action, observation, and reflection. The students who participated were 37 students in class 9 of Mts Nurul Hikmah Bekasi. The research used 2 cycles. In the first and second cycles, the researcher provided explanatory writing material through the picture-to-picture method. The theme of the picture is the picture of natural phenomena. There is an increase of 3 points between cycles 1 and 2. Learning to write through the picture-to-picture method can improve the results of students' ability to write explanatory texts. Teachers are expected to be able to complete this method with several other media, such as augmented reality applications, power points, and several other media. Hence, there are variations in teaching in the classroom.